What Really Matters in Auction Design. - Klemperer, P (2002)
The most important issues in auction design are the traditional concerns of competition policy--preventing collusive, predatory, and entry-deterring behavior. Ascending and uniform-price auctions are particularly vulnerable to these problems. The Anglo-Dutch auction--a hybrid of the sealed-bid and ascending auctions--may perform better. Effective antitrust is also critical. Notable fiascoes in auctioning mobile-phone licenses, television franchises, companies, electricity, etc., and especially the European "third-generation" (UMTS) spectrum auctions, show that everything depends on the details of the context. Auction design is not "one size fits all."